Analisis Tingkat Kepuasan Pelanggan Kereta Api Angkutan Lebaran Di Pulau Jawa - Adi, Wahyu Tamtomo; Aghastya, Adya; Fadilah, Lina Nur (Politeknik Perkeretaapian Indonesia Madiun, 2017)
This research aimed to analyze customer satisfaction level of Lebaran trains in Java Island. Data collection was done through observation and spreading of questionnaires. The sample of this data collection is 206 respondents who traveled during  Lebaran with  train  in  Java  Island.  The  result  of the research by using Importance Performance Analysis method shows that the  respondent's expectation for the train service is 82.8 percent while the respondent's  satisfaction  level  is  65.4 percent. Customer Satisfaction Index for all attributes studied was 71.4 percent.  Some  of  the  attributes  that  need  prioritized  for  improvement  are  considered  inconsistent  with  the  expectations of passengers: cleanliness and comfort toilets in  the  station  and  on the  train,  availability  of facilities for the disabled, affordability of ticket prices and suitability of ticket prices with services. Other attributes that are important and considered satisfactory by  respondens  are  information  boards, station staff  friendliness,  cleanliness  and  convenience  at  the  station,  ticket  service  counter,  train staff  friendliness,  cleanliness  and  convenience  in  trains,  on-time  departure  train,  punctuality   of train arrival, travel time and ease of getting tickets.